Exercise Tolerance in Children with Simple Congenitally Corrected Transposition of the Great Arteries: A Comparative Study - Tony Reybrouck; Marc Gewillig; Werner Budts; Roselien Buys (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Background: The aim of our study was to investigate the exercise capacity of children with congenitally corrected transposition of the great arteries without significant associated heart defects (l-TGA) in comparison with children with the classical type of TGA (d-TGA) and a healthy control group. Methods: Seven children with isolated l-TGA (11.2 ± 3,2 years), 17 children after a Senning operation (13.4 ± 1,6 years ), 26 children with an arterial switch operation (11.0 ± 2,3 years) and 34 healthy controls (12.0 ± 2,9 years) performed a maximal graded cardiopulmonary exercise test on a treadmill, during which oxygen uptake (VO2) and heart rate (HR) were registered.  Results: Significant differences were present between groups for peak VO2(p<0,001) and peak HR (p<0,001). Compared to the control group, l-TGA patients had a significantly lower peak <span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">VO2 (35.4 ± 10.5 mL.<span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">min-1.<span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">kg-1 vs 45.3 ± 8.65 mL.<span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">min-1.<span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">kg-1) and peak HR (161 ± 47 beats. <span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">min-1 vs 193 ± 9 beats. <span style="font-size: 10.5pt; line-height: 107%; font-family: Roboto; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">min-1). Between the arterial switch group and the control group, no significant differences were found, nor between the l-TGA group and the Senning group.  Conclusions: Children with simple l-TGA and children who underwent a Senning procedure for d-TGA have similar exercise capacity, which is significantly lower when compared to arterial switch patients and healthy controls. The underlying mechanism for the impaired exercise capacity seems to be rather HR-related in children with l-TGA, whereas in children with Senning operation reduced right ventricular function and therefore reduced increase in stroke volume with exercise is more present.